2022
DOI: 10.1182/bloodadvances.2021005381
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation analysis in pediatric acute myeloid leukemia

Abstract: We investigated genome-wide DNA methylation patterns in 64 pediatric patients with acute myeloid leukemia (AML). Based on unsupervised clustering with 567 most variably methylated CpG sites, patients were categorized into four clusters associated with genetic alterations. Clusters 1 and 3 were characterized by the presence of known favorable prognostic factors, such as RUNX1-RUNX1T1 fusion and KMT2A rearrangement with low MECOM expression, and biallelic CEBPA mutations (all 8 patients), respectively. Clusters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Tumor suppressor gene methylation is one of the important links in the occurrence of malignant neoplastic diseases and substantially regulates the occurrence and development of malignant neoplastic diseases [ 22 24 ]. Detection of the methylation level of specific genes is one of the important ways to monitor the evolution and outcome of malignant neoplastic diseases [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor suppressor gene methylation is one of the important links in the occurrence of malignant neoplastic diseases and substantially regulates the occurrence and development of malignant neoplastic diseases [ 22 24 ]. Detection of the methylation level of specific genes is one of the important ways to monitor the evolution and outcome of malignant neoplastic diseases [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detection of the methylation level of specific genes is one of the important ways to monitor the evolution and outcome of malignant neoplastic diseases [25]. Acute leukemia is a common hematological malignancy in adults.…”
Section: Discussionmentioning
confidence: 99%
“…66 Limited studies of methylation status in children and inadequate data regarding the efficacy of azacitidine in children AML have restricted its application. 67,68 Moreover, recruitment of patients for maintenance studies has always been difficult.…”
Section: Discussionmentioning
confidence: 99%
“… 66 Limited studies of methylation status in children and inadequate data regarding the efficacy of azacitidine in children AML have restricted its application. 67 , 68 Moreover, recruitment of patients for maintenance studies has always been difficult. A study by Burnett et al 69 showed that only 27% of older patients who were initially enrolled were randomly assigned for maintenance treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Various forms of cancer such as colon, breast, liver, bladder, oesophageal, prostate, and bone cancers, have been reported with aberrant DNA methylation of imprinted sites [8] . Multiple omics-based research studies have also revealed that a variety of malignancies, including hepatocellular carcinoma [9] , glioblastoma, breast cancer, squamous cell lung cancer, thyroid carcinoma, and leukemia [10] , have diverse DNA methylation patterns. Moreover, DNMT mutations, various DNMT expression levels, dysregulation of TETs, and frequent observations of cancer, point towards a strong association between DNA methylation and cancer [11] .…”
Section: Introductionmentioning
confidence: 99%